PENGARUH PEMANFAATAN SIMARI SEBAGAI IMPLEMENTASI PEMBELAJARAN BERBASIS E-LEARNING TERHADAP HASIL BELAJAR MAHASISWA PRODI PENDIDIKAN EKONOMI - Meliyani Meliyani; Supriyanto Supriyanto; Muhammad Rahmattullah (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2019)
Utilization of SIMARI (Integrated Lambung Mangkurat University Information System) as a form of implementation of the application of e-learning in learning, has begun at Lambung Mangkurat University, especially in the Economic Education Study Program since the even semester of the academic year 2017/2018. The problem that arises is that there are still limited subjects applying SIMARI. This study aims to analyze the effect of SIMARI utilization as the implementation of e-learning based learning on the learning outcomes of ULM FKIP Economics Education students. Research uses a quantitative approach. The population in this study were all students of the Economic Education Study Program who had participated in e-learning totaling 291 people. Samples were taken as much as 25%, namely 73 people with stratified sample techniques. Data were collected through questionnaires related to SIMARI utilization in learning as independent variables and documentation of student learning outcomes in subjects that had used SIMARI as the dependent variable. Data were analyzed using simple regression techniques. The results showed that SIMARI utilization in e-learning was in a fairly good category. Student learning outcomes are in a fairly high category. There is a significant effect of SIMARI utilization as the implementation of e-learning based learning on student learning outcomes which is indicated by the Fcount of 4.554 with a significance of 0.036. It was concluded that SIMARI's utilization as an implementation of e-learning in learning could significantly improve student learning outcomes especially in the ULM FKIP Economic Education Study Program.